Age, growth, reproduction and management of Southwestern Atlantic’s largest and endangered herbivorous reef fish, Scarus trispinosus Valenciennes, 1840 - Freitas, Matheus O.; Previero, Marília; Leite, Jonas R.; Francini-Filho, Ronaldo B.; Minte-Vera, Carolina V.; Moura, Rodrigo L. (PeerJ, 2019)
The Brazilian-endemic greenbeack parrotfish, Scarus trispinosus Valenciennes, 1840, is the largest herbivorous reef fish in the South Atlantic. Following the sharp decline of large carnivorous reef fishes, parrotfishes (Labridae: Scarinae) were progressively targeted by commercial fisheries in Brazil, resulting in a global population decline of 50% for S. trispinosus. Most of its remnant population is concentrated in the Abrolhos Bank, where the present study was conducted. We present novel information on age, growth and the reproductive cycle of S. trispinosus, based on 814 individuals obtained from commercial fisheries’ landings and scientific collections, between 2010 and 2013. Sex ratio was biased toward females (1:8), and spawning occurred year-round with discrete peaks in February-March and June-December. Increment analysis indicated annual deposition of growth rings in otoliths, which presented 1–22 rings. The asymptotic length at which growth is zero (L∞) was estimated from a Bayesian logistic regression at 85.28 cm, growth rate (K) at 0.14 year−1, and the theoretical age at zero size (t0) at 0.16. Subregional demographic structuring was detected, with predominance of slower-growing individuals in shallower inshore reefs and predominance of faster-growing and older individuals in deeper offshore sites. We demonstrate that S. trispinosus is highly vulnerable to over-exploitation due to its large size, long live and slow-growth, and review the management measures proposed since its Red List assessment in 2012.
Keywords: Labridae; Scarinae; Fisheries management; Abrolhos; Brazil; Marine Protected Areas; Parrotfishes; Artisanal fisheries; Greenbeack parrotfish